Preventing MRSA Infections in Sports: Effective Strategies and Approaches - Karolina Pawłuszkiewicz; Natalia Kucharczyk; Emilia Kucharczyk (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Infections caused by community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) are a growing concern, particularly among asymptomatic individuals. CA-MRSA can lead to various conditions such as skin infections, septic arthritis, pyomyositis, endocarditis, and pubic osteomyelitis, with athletes being especially vulnerable due to shared equipment, close contact, and skin trauma. Prolonged colonization of the anterior nares and persistence on shared surfaces contribute to its spread. Purpose of work: This study aims to review MRSA prevalence in sports and provide effective strategies for prevention and management.The purpose of this paper is to evaluate MRSA prevalence in sports and provide effective strategies for prevention and management. Materials and methods: A comprehensive analysis of research papers available on PubMed, Google Scholar and Scopus was undertaken using the search terms encompassing the following keywords: Community- acquired MRSA / MRSA and Sport / MRSA and athletes / MRSA Prevention Strategies in Sports / MRSA Infection Risks in Athletes / MRSA Colonization and Sports Participation. Results: A meta-analysis found that about 6% of asymptomatic athletes are colonized with MRSA, though rates vary by sport and country. Decolonization methods may reduce infection risk, but their effects are often temporary. This study examines MRSA colonization and infections in athletes, stressing the importance of preventive measures.